2008
DOI: 10.1016/j.molimm.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced deaminase-mediated class switch recombination is blocked by anti-IgM signaling in a phosphatidylinositol 3-kinase-dependent fashion

Abstract: Activation-induced deaminase (AID) is expressed in activated B lymphocytes and initiates somatic hypermutation and class switch recombination. To determine if different stimuli affect the expression and function of AID, we monitored AID activity in murine B cells stimulated ex vivo with various ligands. AID was rapidly expressed at both the RNA and protein levels following stimulation with LPS, LPS plus IL-4, and anti-CD40 plus IL-4, but was delayed after stimulation with anti-IgM plus IL-4. By day 4, AID was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
15
1
Order By: Relevance
“…This is an important distinction that invites new consideration of existing findings. In contrast to our observation that high-affinity Ag induces upregulation of AID expression, it has previously been shown that AID mRNA expression is delayed and reaches a lower maximum at later days in in vitro murine B cell cultures stimulated with anti-IgM plus IL-4 compared with that in cultures stimulated with LPS and IL-4 (43). In fact, the addition of anti-IgM to cell cultures stimulated with LPS and IL-4 or anti-CD40 and IL-4 was shown to reduce the proportion of class-switched cells in these cultures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is an important distinction that invites new consideration of existing findings. In contrast to our observation that high-affinity Ag induces upregulation of AID expression, it has previously been shown that AID mRNA expression is delayed and reaches a lower maximum at later days in in vitro murine B cell cultures stimulated with anti-IgM plus IL-4 compared with that in cultures stimulated with LPS and IL-4 (43). In fact, the addition of anti-IgM to cell cultures stimulated with LPS and IL-4 or anti-CD40 and IL-4 was shown to reduce the proportion of class-switched cells in these cultures.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, the addition of anti-IgM to cell cultures stimulated with LPS and IL-4 or anti-CD40 and IL-4 was shown to reduce the proportion of class-switched cells in these cultures. Furthermore, these authors reported that B cells stimulated with anti-IgM and IL-4 did not switch to either IgG1 or IgG3 compared with cells stimulated with LPS alone (IgG3 switched) or with LPS and IL-4 (IgG1 switched) (43). However, no difference was found in the levels of germline g1 transcripts of cells stimulated with IL-4 and LPS or anti-IgM, indicating that the inhibitory effect of anti-IgM on switching occurs at a stage subsequent to the formation of the germline transcript.…”
Section: Discussionmentioning
confidence: 99%
“…4 This finding adds to the growing evidence for unique signaling pathways regulating AID expression through the BCR and other surface receptors. 38,39 These studies have shown that signaling through the BCR delays AID expression and down-regulates certain AID-induced processes, such as class-switching, while having no effect on total transcript and protein levels. Furthermore, costimulation of both the BCR and TLR-4 was enough to dampen CSR in a phosphatidylinositol 3-kinase-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, costimulation of both the BCR and TLR-4 was enough to dampen CSR in a phosphatidylinositol 3-kinase-dependent manner. 38 Phosphatidylinositol 3-kinase-signaling interferes with AID activity only when signaled through the BCR, therefore implying a distinct signaling cascade compared with TLR-4. Unlike the BCR and CD40, however, TLR-4 signaling is not known to induce GC formation in vivo; thus, the ex vivo defect reported here might explain why AID deficiency has a GC-specific phenotype regarding apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant AID expression and CSR occurs after stimulation with LPS, which binds to toll-like receptor 4, or with anti-CD40 antibody, which binds to the CD40 receptor. In contrast, AID expression is delayed and CSR is ablated when cells are stimulated with anti-IgM, which binds to the Ig receptor (Heltemes-Harris et al ., 2008; Jabara et al ., 2008). Furthermore, AID expression and CSR are actually suppressed when anti-IgM is added to cells stimulated with LPS or anti-CD40 (Heltemes-Harris et al ., 2008; Jabara et al ., 2008; Rush et al ., 2002).…”
Section: Aid the Master Catalystmentioning
confidence: 99%